Income distribution versus growth. Theory and empirical evidence - Letelier, Leonardo (Estudios de Economía, 2016)
This paper focuses on the relationship between income distribution and growth. It first addresses the theoretical contributions to this issue and secondly it analyzes the empirical evidence available. Three important steps can be distinguished in the theoretical debate. The first one was initiated by D. Ricardo and it deals with factor Income Distribution, a thoroughly relevant theory at the time. The second important step was given by the early neo-Keynesians and the view of the Development Economists, Kuznets being the most prominent representative. Finally the convergence of the endogenous growth models and the so-called new political economy, provides a new interpretation of this economic phenomena. Regarding the empirical evidence, though most of the studies tend to confirm the presence of a significant effect of ID on growth, the existence of a Kuznets type relationship has been questioned.